2012
DOI: 10.1186/1687-1812-2012-91
|View full text |Cite
|
Sign up to set email alerts
|

A product space with the fixed point property

Abstract: We show that the l 1 sum of the van Dulst space with itself possesses the fixed point property, although it fails most of the known conditions that imply (FPP). Mathematics Subject Classification: Primary, 46B20; 47H09.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This space is UNC and hence it satisfies the PS condition (see [52]). Notice that this space is isometric to Proof (See [16]) Indeed, ( 2 , • 2 ) is P-convex, and from Theorem 1.5 in [6] P-convexity is preserved under ∞ -direct sums. Then, 2 ⊕ 1 2 = ( 2 ⊕ 1 2 ) * is P-convex and hence O-convex.…”
Section: Proposition 45 the Van Dulst Space Fails Psz Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…This space is UNC and hence it satisfies the PS condition (see [52]). Notice that this space is isometric to Proof (See [16]) Indeed, ( 2 , • 2 ) is P-convex, and from Theorem 1.5 in [6] P-convexity is preserved under ∞ -direct sums. Then, 2 ⊕ 1 2 = ( 2 ⊕ 1 2 ) * is P-convex and hence O-convex.…”
Section: Proposition 45 the Van Dulst Space Fails Psz Conditionmentioning
confidence: 99%
“…Then, it seems even more unusual to fail to have each one of the above referred properties ANS, OC, PSz and WORTH. But very recently in [16] it has been shown that the space W := V D ⊕ 1 V D enjoys the FPP but it lacks these four geometrical sufficient conditions for FPP. In the same way, in [34] where m = max{a, b √ 2, 2c, d}.…”
Section: Some Pathological Examplesmentioning
confidence: 99%
See 1 more Smart Citation